Towards Global Food Security: Vertical Farming as an Innovative Solution - Dedie Tooy; Encup Supriatna; Muhammad Imam Ma’ruf; La Mema Parandy; Khotimatul Barki (Global Writing Academica Researching & Publishing, 2023)
Vertical farming is becoming the focus of attention as an innovative solution to the challenge of global food security. Urbanization and rapid population growth give rise to the need for efficient agricultural approaches to land use. This research aims to investigate the potential and impact of vertical farming on global food security through a descriptive qualitative approach. The data used in the research comes from various relevant previous research and studies. This research method involves the process of collecting data from scientific literature and previous studies, which are then processed by researchers to produce relevant findings. Through descriptive qualitative analysis, this research highlights the contribution of land use efficiency, adaptation to urban environments, and integration of advanced technologies in the context of vertical farming. The results of this research then found that vertical farming is not only an alternative but also a significant step forward in the transformation of the global agricultural sector. Supportive agricultural regulations and policies, as well as adapting technology to the local environment, are critical challenges in implementing vertical farming. However, opportunities for developing innovations in vertical farming system design and active stakeholder involvement provide a strong foundation for the growth of this industry. This research highlights that vertical farming has great potential to have a positive impact on global food security, by understanding and overcoming existing challenges.